The Effect of Work Competence and Motivation on Teacher Performance: Case Study on Tsanawiyah and Aliyah Madrasah at Pesantren Al-Ma'tuq Sukabumi - Sudrajat, Sudrajat (PT Inovasi Pratama Internasional, 2023)
The competence possessed by the teacher and the work motivation possessed by the teacher as well as the motivation of the leader will improve teacher performance. This study aims to analyze and explain the effect of work competence and motivation on teacher performance. The method used in this study is the quantitative method. The sample in this study was teachers in Madrasah Tsanawiyah and Madrasah Aliyah Al-Ma'tuq totaling 48 respondents. The research data was obtained from the results of filling out the questionnaire, and the analysis method used was multiple regression. From the results of multiple regression data processing, it was obtained that the variables of competence and work motivation had an influence of 72.4% in improving teacher performance, while the remaining 27.6% was influenced by other variables that were not studied. This research discusses theories about human resources and contributes to expanding the literature on teacher competence, work motivation, and performance from an organizational context.